Diversity of the herpotofauna of in Xuan Nha nature reserve, Son La province, northern Vietnam - Sang, Nguyen Van; Dang, Nguyen Xuan; Truong, Nguyen Quang (Academia Journal of Biology, 2012)
﻿This study was conducted during 2006 - 2010, with 7 surveys (June 2006, October 2006, April 2007, May and July 2008, March and September 2010) and duration of 10-20 field-working days per surveys. Totally, 22 survey transects were established within Strict protection zone and Ecological restoration zone of Xuan NhaNR. Each transects were repeated 2-4 times, resulting in total length of surveyed transects of about 350 km. In addition, about 250 local residents and forest rangers were interviewed during the surveys.This study has recorded 39 reptile species and   27 amphibian species. In comparison with   2003 herpetological list, this study adds 7 reptile and 6 amphibian species (species with * in Table 1) to the list, however, it could not record 10 reptile and 1 amphibian species. Combining results of this study with species recorded in 2003 herpetological list gives an updated herpetological list of 50 reptilian species (16 families) and 28 amphibian species (6 families). Of which, 23 species are being threatened, comprising 19 species listed in Red Data Book of Vietnam (2007), eight species listed in the IUCN Red List (2010) and 11 species listed inthe Governmental Decree 32/2006/ND-CP on protection of rare and precious species. This figure indicates high biodiversity conservation significance of Xuan Nha NR. Information on distribution of herpetofauna by different habitat types and current threats to the fauna was also given.